Do we have unrealistic expectations of the potential of immuno-nutrition? - Cynober, L. A. (Canadian Journal of Applied Physiology, 2001)
Heavy sports training schedules and competition is often associated with immuno-suppression, and so there is a theoretical justification for providing athletes with nutrients that display immuno-regulatory properties. Among such immuno-nutrients, considerable attention has been paid in recent years to two amino acids, arginine (ARG) and glutamine (GLN). ARG and GLN availability regulate the function of T lymphocytes, macrophages and polymorphonuclear cells. ARG acts through nitric oxide and polyamine synthesis. The mechanism of action of GLN in immune cells remains unclear. Experience in clinical nutrition suggests that an ARG-enriched diet may limit infectious morbidity in critically ill patients. Data concerning oral/enteral GLN supplementation are more controversial. There have been few trials of supplementation in sports medicine, but results are promising, justifying further studies in which dosages and administration schedules should be taken into account.